Role of miR-613 as a tumor suppressor in glioma cells by targeting SOX9 - Sang, Qiuling; Liu, Xuejuan; Sun, Daju (OncoTargets and therapy, 2018)
MicroRNA-613 (miR-613), a novel cancer-related microRNA, has been shown to be responsible for the inhibition of tumor development and progression in various cancers. We aimed to investigate the biological function and regulatory mechanisms of miR-613 in gliomas. miR-613 expression were detected by qRT-PCR assays in glioma tissues and cell lines. Cell Counting Kit-8 (CCK-8) assay, colony formation analysis, wound healing and transwell invasion assays were performed to evaluate cell proliferation, colony formation, migration and invasion abilities. Luciferase reporter assays, qRT-PCR and Western blot were performed to explore the potential targets of miR-613. Xenograft mice model was established to evaluate the effect of miR-613 in vivo. The expression levels of miR-613 were significantly downregulated in the glioma tissues and cell lines, and the decreased level was significantly negatively associated with the overall disease-free survival of the patients. Functionally, ectopic expression of miR-613 in glioma cells suppressed the proliferation, colony formation, and migration and invasion of the cells. The sex-determining region Y-box 9 (SOX9) was identified as a direct functional target of miR-613, and its expression was inversely correlated with miR-613 expression in glioma tissues. Moreover, rescue of SOX9 could partially reverse the inhibitory effects of miR-613 on glioma cell proliferation, colony formation, migration, and invasion. Importantly, miR-613 also suppressed tumor growth in vivo by targeting SOX9. Taken together, these findings demonstrate that miR-613 functions as a tumor suppressor in glioma cells by directly targeting SOX9.